2003
DOI: 10.5380/avs.v8i2.4027
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade De Leitoas Alojadas Em Gaiolas Individuais Ou Baias Coletivas Durante a Gestação

Abstract: O objetivo do presente estudo foi determinar os efeitos do sistema de alojamento, em gaiolas individuais ou baias coletivas, durante a metade da gestação, no desempenho de fêmeas suínas e de suas leitegadas. Após terem sido inseminadas com 220 dias de idade, em média, as leitoas foram alojadas em gaiolas, até aproximadamente 55 dias de gestação, quando parte delas permaneceram em gaiolas (n=94) e outra parte foi transferida para baias coletivas (n=113), com seis fêmeas/baia. Não houve efeito dos tratamentos na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Regardless of the use of auditory environmental enrichment, no effects of type of housing during gestation were observed on sow reproductive indices, which indicates that the collective housing system may be considered a viable alternative to reduce the time of individual confinement without compromising economic and performance results. Gentilini et al and Bampi et al, [ 32 , 33 ] found no differences in birth rates between the two housing systems, crates or collective pens. Mixed housing, in which sows are kept for about 28 to 35 days in individual crates after artificial insemination, mainly aims to avoid embryo losses, which is influenced by stress due to disputes to establish a social hierarchy or for food [ 9 ]; thus, fights related to social hierarchy may be observed in the first days of regrouping.…”
Section: Reproductive Indicesmentioning
confidence: 96%
See 1 more Smart Citation
“…Regardless of the use of auditory environmental enrichment, no effects of type of housing during gestation were observed on sow reproductive indices, which indicates that the collective housing system may be considered a viable alternative to reduce the time of individual confinement without compromising economic and performance results. Gentilini et al and Bampi et al, [ 32 , 33 ] found no differences in birth rates between the two housing systems, crates or collective pens. Mixed housing, in which sows are kept for about 28 to 35 days in individual crates after artificial insemination, mainly aims to avoid embryo losses, which is influenced by stress due to disputes to establish a social hierarchy or for food [ 9 ]; thus, fights related to social hierarchy may be observed in the first days of regrouping.…”
Section: Reproductive Indicesmentioning
confidence: 96%
“…Additionally, piglets exposed to music had a lower expression of agonistic behaviors and an increased expression of playful behaviors [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The expression of abnormal behaviors, such as stereotypies and excessive aggressiveness, indicate unfavorable welfare conditions [ 40 ], which are related to facility issues and improper animal management, resulting in a decrease in productive performance.…”
Section: Reproductive Indicesmentioning
confidence: 99%